Enhancing Regional Financial Quality: The Role of Government Accounting Standards, Human Resource Capability, and IT Utilization - Yananto Mihadi Putra; Nurul Hidayah; Harnovinsah Harnovinsah; Noor Hazlina Ahmad (Baca Dulu Publisher, 2024)
This research aim to know the effect of gofernment accounting standards, capacity of human resources, and the utilization of information technology on the quality of region’s financial reporting in Central Jakarta. The object for this research was done 60 responden from 13 Unit Kerja Perangkat Daerah (UKPD) of part of financial employee in Central Jakarta. This research used a quantitative approach, using primary data through questionnaries. Data analysis method used in this research is multiple regression with the help of SPSS version 22.0. The result of this research show that either of (t) parsial test the variable of implementation of government accounting standards and internal control system infuelnce on the quality of financial report for local government, however the capacity of human resources no influence on the quality of financial report for local government. And the result from (f) simoultant test the variable implementation of government accounting standards. Capacity human resources, and the utilization of information technology together have a influence on the quality of financial report for local government.